2009
DOI: 10.1007/s00542-009-0876-4
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-ion-implanted air-bearing surface for low-friction head–disk interface

Abstract: With the aim of reducing the lubricant-slider interaction by reducing slider surface energy, we fabricated several types of sliders with fluorine-ion-implanted (FII) air-bearing surfaces by using different levels of acceleration voltage for FII. With a low acceleration voltage, the fluorine-ions tended to be concentrated at shallower depths from the slider surface, and the contact angle of the water droplets was greater. The FII-treated slider showed lower touch-down height, which implies an improvement of sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Existing research has concluded that the intermolecular force can be changed by changing either surface energy or nominal contact area or roughness/mean asperity radius. The direct approaches to reduce intermolecular force include getting the slider FII-treated [51] and use of spherical pad slider design [48].…”
Section: Nonlinear Dynamics Of Slider In Sub-10 Nm Clearance Regimementioning
confidence: 99%
“…Existing research has concluded that the intermolecular force can be changed by changing either surface energy or nominal contact area or roughness/mean asperity radius. The direct approaches to reduce intermolecular force include getting the slider FII-treated [51] and use of spherical pad slider design [48].…”
Section: Nonlinear Dynamics Of Slider In Sub-10 Nm Clearance Regimementioning
confidence: 99%